Composition of the Green Oil in Hydrogenation of Acetylene over a Commercial Pd‐Ag/Al2O3 Catalyst. Issue 5 (5th April 2016) - Zhang, Jian; Sui, Zhijun; Zhu, Yi‐An; Chen, De; Zhou, Xinggui; Yuan, Weikang
Abstract: Selective acetylene hydrogenation over a commercial Pd‐Ag/Al2 O3 catalyst was carried out under industrial operation conditions that correspond to the "tail‐end" process. Pyrolysis gas chromatography‐mass spectrometry was used to analyze the composition of the green oil. C8–C30 linear hydrocarbons with even carbon‐numbered chains were detected as the main components of the green oil. Its chain length increased with operating time, temperature, and hydrogen partial pressure, and decreased with acetylene partial pressure. The composition of the green oil deviates from the Anderson‐Schulz‐Flory distribution. Both coupling‐hydrogenation and hydrogenation‐coupling mechanisms are involved in green oil formation. Abstract : The composition evolution of green oil which is formed during acetylene selective hydrogenation over a commercial Pd‐Ag catalyst is investigated by pyrolysis gas chromatography‐mass spectrometry and other methods and reaction routes are proposed. The results are valuable to avoid green oil formation in industrial processes and for the development of new catalysts.